The Eurosystem's asset purchase programme and TARGET balances - Jens Eisenschmidt; Danielle Kedan; Martin Schmitz; Ramón Adalid; Patrick Papsdorf (European Central Bank (ECB), 2017)
TARGET balances have risen during the period of the Eurosystem's asset purchase programme (APP). The APP gives rise to substantial cross-border flows of reserves at the time of asset purchases and beyond, reflecting the interaction of decentralised monetary policy implementation and the integrated euro area financial structure. This financial structure, in which only a handful of locations act as gateways between the euro area and the rest of the world, leads to rising TARGET balances at the time of APP purchases and the persistence of TARGET balances in the context of subsequent portfolio rebalancing. TARGET balances per se are not necessarily an indicator of stress in bank funding markets, financial market fragmentation or unsustainable balance of payments developments.
Keywords: E58; G02; F32; 330; TARGET2; financial structure; asset purchase programme; excess liquidity; balance of payments